A Late Prosthetic Mitral Valve Infective Endocarditis Caused by Micrococcus spp. that Fully Recovered by Antibiotics Treatment : A Rare Case - Imam Mahbub Zam Zami; Agus Subagjo (Universitas Airlangga, 2022)
Prosthetic valve endocarditis is the most severe form endocarditis with prevalence of 5.7% at 5 years and mortality with medical treatment is 26%-75%. Case Summary: Male, 46 years old, with mechanic mitral prosthetic valve >5 years, hemiparesis sinistra due to embolic stroke >4 weeks prior, was suffering from persistent fever >38,5⁰ for 2 weeks without heart failure. Three separate blood cultures came positive with Micrococcus spp. and Osler’s node was noticed. Echocardiography shown 1.0 cm x 0.9 cm vegetation at mitral prosthetic valve without paravalvular leakage. Patient was assessed as late mitral PVE. Discussion: Gentamycin, Levofloxacin, and Erythromycin were given based on susceptibility test continued by Meropenem as therapy of urinary tract infection based on susceptibility test after second blood culture result was negative. The patient underwent 42 weeks of antibiotics course. The patient was discharged with good condition, no signs and symptoms of infection or heart failure, blood test was within normal limit, no vegetations with prosthetic mitral valve functioned normally. This case shows that late PVE caused by Micrococcus spp. can be treated by 42 weeks course of antibiotics according to microbial susceptibility test.